Size effect on magnetic susceptibility of titanium monoxide nanocrystals. Issue 2 (26th October 2015) - Valeeva, Albina A.; Nazarova, Svetlana Z.; Rempel, Andrey A.
Abstract : For the first time a magnetic quantum‐size effect is found in paramagnetic titanium monoxide nanocrystals with the sizes down to 30 nm. In situ measurements in the temperature range from 300 to 1200 K showed that the magnetic susceptibility of superstoichiometric titanium monoxide nanocrystals TiO y ( y  > 1) depends not only on the structural state of the sample, but also on the size of nanocrystals. The data analysis both for the ordered and disordered TiO y showed that the reason for inversely proportional dependence of Van‐Vleck paramagnetism on the size of titanium monoxide nanocrystals is distortion of local symmetry of titanium and oxygen atoms near the nanocrystal surface. Van‐Vleck contribution induced by the atomic‐vacancy disordering in titanium monoxide is proportional to the deviation of the long‐order parameter from its maximal value.